5G carrier network data collection and security management evolution ideas - Huifang HOU; Xuefang LI; Jie PAN; Zhigang DING (Dianxin kexue)
Operators collect user data by deploying DPI system at some network node,and combining with the security control system to achieve an operator-level security operation and management system.The new architecture,technologies and services of the 5G network meet the unprecedented demands of connection,but also bring new security risks.The evolution of the data collection scheme of the carrier network was mainly discussed under the background of 5G network,as well as the innovative ideas of content security and network security systems that follow.